Edukasi Gizi Cegah Stunting bagi Orang Tua di Desa Kesetnana, Kabupaten Timor Tengah Selatan - Maria Sambriong; Elisabeth Herwanti; Yoany Maria Vianney B. Aty (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
The number of toddlers experiencing malnutrition in the South Central Timor district fluctuated from 2013 to 2017 ranging from 3-12 cases. The prevalence of stunting in the Kesetnana village in 2021 reached 48.3% or the highest in NTT. Based on this, it is necessary to provide nutritional assistance for children under five for parents. The purpose of this activity is to reduce the number of stunting cases that occur. The method used in this activity is screening and education about stunting, exclusive breastfeeding, breast care and balanced nutrition food processing practices. The location of the activity is Dusun D, Kesetnana village, TTS. The participants were breastfeeding mothers, pregnant women and toddlers and school-aged children. The media used were booklets, leaflets, banners, breast phantoms, samples of healthy food and cooking utensils. The result of this activity is that the knowledge of parents becomes very good about stunting, exclusive breastfeeding, breast care and can practice processing balanced nutritional foods again. Assistance activities to the village community continue to be continued by both health workers and health cadres, community leaders in the village. ABSTRAK Jumlah Balita yang mengalami gizi buruk di wilayah kabupaten Timor Tengah Selatan fluktuatif sejak tahun 2013 sampai dengan 2017 berkisar 3-12 kasus. Prevalensi stunting di desa kesetnana tahun 2021 mencapai 48,3% atau paling tinggi di NTT. Berdasarkan hal ini maka perlu dilakukan Pendampingan gizi Balita bagi para orang tua. Tujuan kegiatan ini adalah agar dapat mengurangi jumlah kasus stunting yang terjadi. Metode yang digunakan dalam kegiatan ini adalah skrining dan edukasi tentang stunting, ASI ekslusif, perawatan payudara dan praktek pengolahan makanan gizi seimbang. Lokasi kegiatan yakni Dusun D desa Kesetnana, TTS. Pesertanya ibu menyusui, Ibu hamil dan balita serta anak usia sekolah Media yang dipakai adalah booklet,leaflet, spanduk, phantom payudara, contoh makanan sehat dan peralatan masak. Hasil dari kegiatan ini adalah pengetahuan para orang tua menjadi sangat baik tentang stunting, ASI ekslusif, perawatan payudara dan dapat mempraktekan kembali pengolahan makanan gizi seimbang. Kegiatan pendampingan kepada masyarakat desa kesetnana terus dilanjutkan baik oleh petugas kesehatan maupun para kader kesehatan, tokoh masyarakat yang ada di desa tersebut.